"The Indians of every denomination were free, and independent of us": Anglo-Virginian explorations of indigenous slavery, freedom, and society, 1772–1830. Issue 2 (3rd May 2016) - Ray, Kristofer
ABSTRACT: In arguing against Indian slavery, plaintiff's attorneys in the 1772 Virginia General Court case Robin v Hardaway faced a dilemma: how could they condemn enslavement while mollifying public conviction that Indigenous "savagery" made them dangerous to community stability? Their solution, rooted in a nearly two-century discourse of slavery and freedom, was to insist that Indians derived from independent polities (unlike other enslaved communities). As such, they were both inherently free and outside the evolving Anglo-American body politic, and whites could legitimately deprive them of property, happiness, and safety. Subsequent Virginia freedom cases contributed to the discourse employed in Robin, as did early-nineteenth-century US Supreme Court decisions. It came to underpin civilization policies as well as removal, once older understandings of Anglo-American "civility" became untenable to Southern whites.